Investor sentiment and equity mutual fund performance in Brazil - Da Silva, Sabrina Espinele (2025)
Purpose: Focusing on the Brazilian equity mutual fund industry, this study analyzes whether including the investor sentiment index in asset pricing models is important for explaining fund alpha. Design/methodology/approach: The investor sentiment index and risk factors in the Fama and French (1993) and Carhart (1997) models were estimated, the risk-adjusted performance of a sample of equity mutual funds in Brazil was evaluated, and a United States (US) sample was included for a complementary perspective. The sample period spans 2010–2019 for Brazil and 2010–2018 for the US. Findings: The results contrasted with those evidenced in the US, where the sentiment index was an important factor in explaining the probability of alpha occurrence, especially in the case of winner funds, defined as those exhibiting a positive and statistically significant alpha at the 5% level. Overall, the findings suggest that, in the Brazilian market, pricing models incorporating investor sentiment as an additional factor fail to adequately capture the outperformance probability of equity mutual funds. These results suggest that the factors influencing fund performance may differ between the two countries and highlight the relevance of developing more suitable investor sentiment indicators for emerging markets. Originality/value: This study examines the impact of the sentiment index on the performance of equity mutual funds in Brazil, specifically its influence on alpha generation.